Answer:
Step-by-step explanation:
Answer:;4.4
Step-by-step explanation: Since it varies inversely we know G times H squared is equal to some constant, k. So we have G*H*H=k. We are told that when H=4, G=.25. Plugging this in, we have .25*4*4=k. This simplifies to 4=k. Our new equation is G*H*H=4. Now, we want to solve for G when H=.3. We plug it in. G*.3*.3=4 => G*.09=4. G=4/.09. This means G is approximately 44.4.
Answer:
the action or process of transmitting something, or the state of being transmitted.
Answer:
<h2>x + 2y = 8</h2>
Step-by-step explanation:
The standard form of an equation of a line:
We have:
Convert:
<em>multiply both sides by 2</em>
<em>add x to both sides</em>
I think he lost $375 because I'm pretty sure your supposed to multiply 55 and 7